Maternal mortality in Ghana: an exploration of partners’ perception about factors that contributed to their wife’s death - Adika, Diana Mawuko; Chutiyami, Muhammad; Dathini, Hamina; Adamu, Haruna (International Journal Of Community Medicine And Public Health, 2017)
Background: Many programmes were put in place internationally and locally to curtail the menace of maternal mortality, but little achievement has been made in certain parts of the world, particularly in sub-Saharan Africa. A number of literatures exist, which investigate into the predisposing factors of maternal mortality in Ghana, however, no published evidence as the time of conducting this study explore the perception of men with respect to maternal mortality. This study aims to explore the perceptions of men who have lost their wives about the factors that contributed to their wife’s death in Accra, Ghana. Methods: A qualitative phenomenological approach was adopted, using an in-depth semi-structured interview conducted via a phone call, which was recorded and transcribed. Ten men participated in the study. The data was analysed using narrative synthesis through identification of themes/sub-themes. Results: It was identified that physical, cultural and socio-economic factors were responsible for the death of men’s wives on the course of pregnancy. The major physical factors include direct causes of maternal mortality notably haemorrhage, delay in reaching health facility and delay from the health facility. The cultural factors mainly include seeking care from unskilled attendants and use of traditional preparations to aid delivery. Lastly, poor socio-economic status was blamed by majority of the participants, which impedes them from accessing quality care within shortest period of time. Conclusions: Men perceived factors predisposing to maternal mortality in Accra, Ghana were avoidable with quality health care services and improved access to the health facilities.